2019
DOI: 10.1080/21691401.2019.1629950
|View full text |Cite
|
Sign up to set email alerts
|

Vacuolar protein sorting 4B regulates the proliferation and odontoblastic differentiation of human dental pulp stem cells through the Wnt-β-catenin signalling pathway

Abstract: Our previous studies have revealed that a dominant mutation in vacuolar protein sorting 4B (VPS4B), a member of the AAA ATPase family, causes dentin dysplasia type I. The purpose of the present study was to investigate the roles of VPS4B in human dental pulp stem cells (hDPSCs) and to elucidate the underlying molecular mechanisms. In this study, we found that VPS4B was highly expressed in the dental pulp cells of the mouse molar tooth germ, and the expression of VPS4B increased significantly during the odontob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…This could be further supported by previous research reporting that the expression of β-catenin was significantly upregulated during odontogenic differentiation of DPSCs, and knockdown of βcatenin disrupted odontogenic differentiation, which could be reversed by the lithium chloride-induced accumulation of βcatenin (Han et al, 2014). Besides, mounting evidence shows that numerous regulators, including but not limited to enhancer of zeste homolog 2, Stathmin, vacuolar protein sorting 4B, R-Spondin 2, and lncRNA DANCR, regulate the odontogenic differentiation of DPSCs through the Wnt/β-catenin pathway (Chen et al, 2016;Li et al, 2018;Pan et al, 2019;Zhang et al, 2019;Gong et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This could be further supported by previous research reporting that the expression of β-catenin was significantly upregulated during odontogenic differentiation of DPSCs, and knockdown of βcatenin disrupted odontogenic differentiation, which could be reversed by the lithium chloride-induced accumulation of βcatenin (Han et al, 2014). Besides, mounting evidence shows that numerous regulators, including but not limited to enhancer of zeste homolog 2, Stathmin, vacuolar protein sorting 4B, R-Spondin 2, and lncRNA DANCR, regulate the odontogenic differentiation of DPSCs through the Wnt/β-catenin pathway (Chen et al, 2016;Li et al, 2018;Pan et al, 2019;Zhang et al, 2019;Gong et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that VPS4 affects extracellular secretion and lysosomal and cell proliferation and differentiation through regulating specific signaling pathways. 32,33 Some scholars found that the level of VPS4B in the brain tissues was significantly increased after MCAO and the activity of caspase-3 protein was up-regulated to contribute for neuron apoptosis. 34 Our study further demonstrated that VPS4B was a direct target of miR-488-3p and verified that miR-488-3p could inhibit the expression of VPS4B in OGD/R-treated neurons.…”
Section: Discussionmentioning
confidence: 99%
“…of human dental pulp stem cells (hDPSCs). 32 In Parkinson's Disease, VPS4 acts as the target site of alphasynuclein (α-SYN) in regulation of lysosomal or extracellular secretion, leading to intercellular propagation of Lewy pathology. 33 It was found that VPS4B level was significantly increased in the hippocampus of adult mice with Middle Cerebral Artery Occlusion (MCAO).…”
mentioning
confidence: 99%
“…Until now, few studies have compared cell proliferation between patients with DD-I and healthy individuals. One study 39 performed proliferation assays using Cell Counting Kit-8, which indicated that human dental pulp stem cells (hDPSCs) transduced with an shRNA-Vps4b lentivirus proliferated slower than their counterparts transduced with a control lentivirus over 7 days. However, in our study, the DD-I DFCs growth rates were significantly increased compared to the control DFCs growth rates after 3 days of culture.…”
Section: Discussionmentioning
confidence: 99%
“… 41 43 One study showed that VPS4B acts as a regulator of hDPSC proliferation and differentiation via Wnt-β-catenin signaling. 39 Moreover, it has been demonstrated that the overexpression or knockdown of VPS4B in human gingival fibroblasts markedly increased or decreased the expression of CHMP4B, Wnt5a, and β-catenin. The VPS4B -CHMP4B-Wnt5a-β-catenin regulatory pathway might regulate odontoblast differentiation and root formation.…”
Section: Discussionmentioning
confidence: 99%